2019
DOI: 10.1111/jop.12858
|View full text |Cite
|
Sign up to set email alerts
|

Primary oral leiomyosarcoma: A systematic review and update

Abstract: The aim of this systematic review was to address the clinicopathologic inconsistencies noted with primary oral leiomyosarcoma in the literature by amassing the available data published into a comprehensive analysis. Eligibility criteria included publications of cases with dedicated immunohistochemical work‐up along with radiographs to evaluate location. Based on these criteria, the systematic review compiled 29 cases. Four primary location sites were identified in the reported cases: soft tissue presentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…There was also one unusual case found in the buccal area of the temporomandibular joint. However, Ko 17 reported that the most common location for primary oral leiomyosarcoma seems to be soft tissue, and not the jawbones, as frequently reported. Further research is needed to clarify this point.…”
Section: Discussionmentioning
confidence: 90%
“…There was also one unusual case found in the buccal area of the temporomandibular joint. However, Ko 17 reported that the most common location for primary oral leiomyosarcoma seems to be soft tissue, and not the jawbones, as frequently reported. Further research is needed to clarify this point.…”
Section: Discussionmentioning
confidence: 90%
“…However, oral and maxillofacial leiomyosarcoma has been reported in several sites, including the mandible, tongue, and buccal mucosa, in patients aged between seven to 67 years. Soft tissue lesions present as pedunculated soft tissue mass [16]. The tumour cells exhibit blunt-ended cigar nuclei, deeply eosinophilic fibrillary cytoplasm, and perinuclear vacuoles, arranged in a fascicular pattern [17].…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcoma is a malignant tumor of smooth muscle derivation which account for 5%---10% of all soft tissue sarcomas. 3,10 LMS frequently affects the retro-peritoneal region, the uterus and the gastrointestinal tract. 1,11 Oral LMS are extremely rare, accounting for 0.64% of all LMS and for 5.7% of head and neck LMS.…”
Section: Discussionmentioning
confidence: 99%
“…1 Due to the lack of smooth muscle tissue in the oral cavity, it has been suggested that LMS arise from smooth muscle cells of the blood vessel walls, circumvallate papillae of the tongue, neuromuscular bundles, myoepithelial cells or pluripotent undifferentiated mesenchymal cells. 1,3,4 Clinically, sarcomas of the oral cavity show nonspecific signs and symptoms and can appear as primary tumors, radiation-associated tumors or metastatic tumors. 1,4,5 Biopsy, histological examination and immunohistochemical staining are mandatory to achieve a definitive diagnosis.…”
Section: Introductionmentioning
confidence: 99%